Implementasi Online Peer Assesment pada Pembelajaran Bauran - Hartoto Hartoto; Sella Mawarni; Muhammad Rais (Universitas Negeri Makassar, 2023)
This study describes the implementation of online peer assessment which was carried out in blended learning in Information and Communication Technology courses in elementary schools involving 143 students. The online peer assessment is carried out through 6 stages, namely 1) the design stage, 2) the perception leveling stage, 3) the task collection stage, 4) the assessment stage, 5) the assessment objection stage, and 6) the value determination stage. Each stage is described qualitatively. Through online peer assessment, students are more actively involved in the learning process, easing the lecturer's task in conducting assessments, and the learning outcomes obtained show high scores so as to help achieve learning objectives.